Penggunaan Gadget dan Dampaknya terhadap Prestasi Akademik Siswa di SMK Assalam Kabupaten Bandung - Aden Fadhli Wahyu Pratama; Indah Ariyani; Indah Arifin, Lisfa; Muhammad Septian; Muhsin (Jurnal Dirosah Islamiyah, 2024)
This study is motivated by the problem of gadget use and its impact on student academic achievement at SMK Assalam Bandung Regency. Nowadays, the use of gadgets among students has become a common phenomenon, both giving positive and negative impacts on their learning process. This research uses a qualitative approach with descriptive methods and collects data through observation, interviews, and documentation in the field. The results show that the gadget use policy at SMK Assalam affects students' use patterns in the learning process, with rules that regulate the use of gadgets only when needed in learning. The positive impacts include wide access to information and easier communication between students and teachers, while the negative impacts include disruption of learning focus, students falling behind on subject matter, and potential addiction to useless applications. This study suggests the need for wise management of gadget use in schools to maximize its benefits in supporting students' academic achievement.